Air Pollution Assessment of Thermal Power and Cement Plants in Ninh Binh Province - Anh Le, Hoang; Anh Tuan, Ngo; Minh Thuy, Kim; Thi Viet Anh, Pham; Thu Huyen, Pham (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1S, 2024)
Cement production and thermal power generation are two primary industries in Ninh Binh province, but they are also among the sources of emissions that can negatively affect to local and regional air quality. This study employs the AERMOD air dispersion modeling system to assess the air pollution levels caused by the operations of the cement and thermal power plants in Ninh Binh province. The results show that the highest average hourly concentrations of TSP, SO 2 , and NO x are 30.1 µg/m 3 , 73.2 µg/m 3 , and 361 µg/m 3 , respectively; the highest average daily concentrations are 3.77 µg/m 3 , 2.17 µg/m 3 , and 49.0 µg/m 3 , respectively. The predominant direction of pollutant dispersion is towards the West and Southwest, affecting areas within Ninh Binh City and Tam Diep City. The AERMOD model results indicate that pollutant concentrations are lower than the relevant national technical standards. However, it is concerning that a small region within Cuc Phuong National Park shows signs of being affected by these air pollutants. Therefore, stringent control measures on emissions from thermal power and cement plants must be in place to ensure the local air quality and public health.